The Therapeutic Nurse-Patient Relationship in Hemodialysis: A Pilot Mixed-Method Study on the Perceived Quality of Nurses' Attitudes and Caring Behaviors - Claudia Camedda; Gloria Bici; Camilla Elena Magi; Alice Guzzon; Yari Longobucco (MDPI AG, 2023)
Chronic kidney disease affects many people around the world, leading those affected to replacement therapy such as hemodialysis. People who undergo hemodialysis generally undertake 2-3 treatments per week, lasting about 3-4 h each; patients spend many hours per week in contact with nurses, building a therapeutic relationship. The purpose of this work is to assess the quality of nurses' perceived caring attitudes and behaviors and to determine their perceptions regarding the importance of the therapeutic relationship with the assisted patients. A self-reported questionnaire composed of three sections was administered to nurses; the first section included sociodemographic questions, the second the Caring Nurse-Patient Interaction Scale (CNPI-23), and the third part of the questionnaire was composed of open-ended questions investigating patients' expectations according to nurses, the relevance of the therapeutic relationship on their work, and its effect on themselves and/or their own job satisfaction. Statistically significant correlations and trends have been observed between nurses' sociodemographic data and the CNPI-23 items. In the clinical care area, nurses who have a post-basic degree or more years of experience feel more competent than those in other categories; in the relational care area, women tend to feel more competent than men. No correlations were found between the humanistic and comfort care areas. According to the results, the post-basic training of dialysis nurses and the adoption of organizational strategies that encourage nurse retention should be enhanced. This study was not registered.